Ingeolysis (nice, fr solution) (2020)
A collection of data regarding problems, observations and breakdowns of the sewerage and wastewater system in the city of Nice in France has been recorded the past few years by both city workers and citizens. The nature of the data is mainly reports of the time and location of a failure along with some observations and classifications of said reports. Given the amount of data collected, an analysis was in order but extracting relevant information from written data can be a challenge. Also, there currently exists no established relationship between the temporal or spatial variability of the reports, and the state of the system and its structural variables. With these challenges and the nature of the information collected in mind, an interactive visualization solution was designed. The solution was developed entirely in JavaScript, HTML and CSS using a library called D3.js. Hopefully, this solution will facilitate the establishment of relations between time, location and nature of a report so as to enable analysts to extrapolate the behavior of failures within the city with the purpose of preventing or reacting to problems in the sewerage and wastewater system. Simultaneously, the tool will enable its user to analyze the data seen, in order to identify its composition and problems allowing for some insight over the way data is collected. Visualizations such as a map, bar graph and pie chart were used among others to create the tool.